Invasive bacterial infections in Gambians with sickle cell anemia in an era of widespread pneumococcal and hemophilus influenzae type b vaccination. Issue 49 (December 2016) - Soothill, Germander; Darboe, Saffiatou; Bah, Gibril; Bolarinde, Lawal; Cunnington, Aubrey; Anderson, Suzanne T.
Abstract : Abstract: There is relatively little data on the etiology of bacterial infections in patients with sickle cell anemia (SCA) in West Africa, and no data from countries that have implemented conjugate vaccines against both Streptococcus pneumoniae and Haemophilus influenzae type b (Hib). We conducted a retrospective analysis of SCA patients admitted to the Medical Research Council Unit, The Gambia, during a 5-year period when there was high coverage of Hib and Pneumococcal conjugate vaccination. We evaluated 161 admissions of 126 patients between April 2010 and April 2015. Pathogenic bacteria were identified in blood cultures from 11 of the 131 admissions that had cultures taken (8.4%, 95% CI 4.5–14.1%). The most frequent isolate was Salmonella Typhimurium (6/11; 54.5%), followed by Staphylococcus aureus (2/11; 18.2%) and other enteric Gram-negative pathogens (2/11; 18.2%) and there was 1 case of H influenzae non-type b bacteremia (1/11; 9.1%). There were no episodes of bacteremia caused by S pneumoniae or Hib. The low prevalence of S pneumoniae and Hib and the predominance of nontyphoidal Salmonella as a cause of bacteremia suggest the need to reconsider optimal antimicrobial prophylaxis and the empirical treatment regimens for patients with SCA.